Uwagi o dworze królewskim w podróży. Na przykładzie wyprawy Zygmunta III do Szwecji w latach 1593-1594 - Mira Belzyt (In Gremium. Studies in History, Culture and Politics, 2013)
Notes on royal court on a journey; based on Sigismund III expedition to Sweden in the years 1593-1594The king of Poland and the Grand Duke of Lithuania Sigismund III Vasa (1587-1632) ruled similarly short in Sweden as well, actually his reign covers the period from 1592-1599. In this period, he visited his motherland twice. The first journey in the years 1593-1594 was a coronation expedition. This article discusses the composition of the Polish-Lithuanian court during the first journey. Court accounts as of 1595 published in 1934 by Wanda Dobrowolska provide vital information on the subject.It is estimated that the royal court during the journey consisted of at least 75 people who were named in the court accounts. The total number together with the Queen Anna’s and the king’s daughter Anna Vasa’s woman’s room – without the armed guards – certainly amounted to over 100 people. Among them there were high officials like vice-chancellor Jan Tarnowski as well as the King’s secretary, the Queen’s chancellor Stanisław Fogelweder together with the court service. Special attention attracts a great number of 23 musicians which make 30% of all the people named in the accounts. Diminished as compared to the court in Wawel, the court on the journey, fulfilled well, as one may assume, its functions as the centre of power, the tool to satisfy the basic needs of the King and his family at the appropriate level, and as a tool to entertain the royal family.